Budaya Mutu Dalam Pelayanan Pendidikan - Muhammad Basri (Department of Government Studies Universitas Muhammadiyah Makassar, 2011)
Educational services in schools is part of the community and the public school. Service quality is a product and or services in accordance with established quality standards and customer satisfaction. Quality in education include the quality of input, process, output, and outcome. Input-grade education when it is ready to proceed otherwise. The process of quality education to create an atmosphere where learning is active, innovative, creative, effective, dan fun. Output otherwise qualified if the learning outcomes of academic and non academic students achieving at least equal to the minimum completeness criteria specified. Outcome graduates expressed significantly faster when absorbed in the world of work, fair wages, all parties acknowledge and satisfied with the intelligence, skill, personality. Government's efforts to service and quality of education is the use of School-Based Management (SBM) is accompanied by the determination of output criteria, processes, and educational input at school. Expected Output school student achievement / school both academic and non academic generated meets the specified criteria. (2) process, ie, among others: the effectiveness of teaching and learning process, schools have the teamwork of a compact, intelligent and dynamic, the school has the authority (autonomy), school evaluation and continuous improvement, (3) input, ie, among other : the school has: policies, goals, and quality objectives are clear, available resources, feasible, and highly dedicated.Pelayanan pendidikan di sekolah adalah bagian dari masyarakat dan sekolah umum. Kualitas layanan adalah produk dan atau jasa sesuai dengan standar kualitas yang ditetapkan dan kepuasan pelanggan. Kualitas dalam pendidikan termasuk kualitas input, proses, output, dan hasil. Input-kelas pendidikan bila sudah siap untuk melanjutkan sebaliknya. Proses pendidikan yang berkualitas untuk menciptakan suasana di mana pembelajaran aktif, inovatif, kreatif, efektif, menyenangkan Dan. Keluaran dinyatakan memenuhi syarat jika hasil belajar siswa akademik dan non akademik mencapai paling tidak sama dengan kriteria kelengkapan minimal yang ditetapkan. Lulusan Hasil mengungkapkan secara signifikan lebih cepat ketika diserap di dunia kerja, upah yang adil, semua pihak mengakui dan puas dengan, keterampilan kepribadian kecerdasan,. Upaya Pemerintah untuk pelayanan dan kualitas pendidikan adalah penggunaan Manajemen Berbasis Sekolah (MBS) disertai dengan penentuan kriteria output, proses, dan input pendidikan di sekolah. Keluaran sekolah diharapkan prestasi siswa / sekolah dihasilkan akademik baik akademis dan non memenuhi kriteria yang ditentukan. (2) proses, yaitu, antara lain: efektivitas proses belajar mengajar, sekolah memiliki teamwork yang kompak, cerdas dan dinamis, sekolah memiliki kewenangan (otonomi), evaluasi sekolah dan perbaikan terus-menerus, (3) input, yaitu, antara lain: sekolah memiliki: kebijakan, tujuan, dan sasaran mutu yang jelas, sumber daya yang tersedia, layak, dan berdedikasi tinggi.